2020
DOI: 10.1021/acs.est.9b06111
|View full text |Cite
|
Sign up to set email alerts
|

Facet-Dependent Adsorption and Fractionation of Natural Organic Matter on Crystalline Metal Oxide Nanoparticles

Abstract: Natural organic matter (NOM) and crystalline metal oxide nanoparticles are both prevalent in natural aquatic environments, and their interactions have important environmental and biogeochemical implications. Here, we show that these interactions are significantly affected by an intrinsic property of metal oxide nanocrystals, the exposed facets. Both anatase (TiO2) and hematite (α-Fe2O3) nanocrystals, representing common engineered and naturally occurring metal oxides, exhibited apparent facet-dependent adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 69 publications
0
41
0
Order By: Relevance
“…S5 †), and are consistent with previous observations that the fluorescent components of NOM, corresponding to fulvic-like substances, exhibited strong complexation abilities toward soft and transition metals. 47,48 More importantly, the different extents of NOM-Hg binding may explain the stronger inhibiting effect of SRFA vs. SRHA on the growth of tiemannite nanoparticles, as the chemical binding of surface modifiers is expected to mitigate the crystal growth of the initial precipitation products via reducing the surface energy. [49][50][51]…”
Section: Environmental Science: Nano Communicationmentioning
confidence: 99%
“…S5 †), and are consistent with previous observations that the fluorescent components of NOM, corresponding to fulvic-like substances, exhibited strong complexation abilities toward soft and transition metals. 47,48 More importantly, the different extents of NOM-Hg binding may explain the stronger inhibiting effect of SRFA vs. SRHA on the growth of tiemannite nanoparticles, as the chemical binding of surface modifiers is expected to mitigate the crystal growth of the initial precipitation products via reducing the surface energy. [49][50][51]…”
Section: Environmental Science: Nano Communicationmentioning
confidence: 99%
“…The mutual interaction between Fe oxides and OM molecules significantly depends on the physicochemical properties of the Fe oxides, such as the particle size, , surface charge, solubility, and crystallinity . It has been reported that Fe oxides with poor crystallinity, more defects, and small size can be more easily reduced. , The results of recent theoretical calculations and experimental evidences showed that the inherent characteristics of exposed facets of Fe oxides play significant roles in determining their binding affinities to OM or low-molecular-weight organic acids. During physical and chemical adsorption, different exposed facets of metal oxides are the key factors determining the ligand-exchange and hydrophobic interaction between Fe oxides and OM. , Despite these progresses, there are still knowledge gaps regarding the dynamic interaction between facet-dependent Fe oxides and OM during dissimilatory Fe reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous studies showed that the exposed facets affect the adsorption of proteins and heavy metals, the decomposition of organic pollutants on metal oxides, , and the mobility and fate of OM components. , The combination between Fe oxides and OM is mainly driven by surface complexation between carboxyl groups in OM and surface Fe atoms. During the adsorption process, OM molecules with a high oxidation state and high aromaticity preferentially form ligand-exchange complexes with hydroxyl functional groups on the hematite surface, and OM components with low molecular weight exhibit a strong facet-dependent selective fractionation . Although the importance of the Fe oxide reductive dissolution process to the fate of Fe-bound OM was well recognized, the fate of Fe oxide-bound OM at the molecular scale remains unclear. , Specifically, characteristic variations of the OM during the reductive dissolution of Fe remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations